Potential Uses Of The By-Product From The Lime/Limestone Scrubbing Of SO2 From Flue Gases ? Introduction - W. C. Taylor (Society for Mining, Metallurgy & Exploration, 1974)
The present fuel situation indicates that, at least for the next 20 to 30 years, the burning of coal will be a main source of energy. All coal contains sulfur, which is converted to sulfur dioxide during combustion. The concentration of sulfur dioxide (SO2) in the resulting flue gas, for most coals, would exceed the limits established by the Environmental Protection Agency (EPA). Therefore, the sulfur must either be removed from the coal prior to its burning, or be collected from the stack gas before it reaches the atmosphere. There is currently a large amount of research devoted to methods of removing the sulfur from the coal before burning, or during combustion in fluidized beds with materials which trap the sulfur in the solid residue. The commercialization of these processes, however, is not expected in the near future. Flue gas desulfurization appears to be the best near term prospect of fulfilling current air quality control regulations. The lime/limestone wet-scrubbing methods are the most advanced flue gas desulfurization processes and will account for the majority of sulfur removal systems in electric power generation. There are currently at least 23 full-scale systems existing or under construction and 17 of these will use the lime or limestone wet-scrubbing process. (1)